Biodiversity and species composition of xerothermic grassland patches following removal of shrubs and trees from the ecotone zone within the Polana Polichno reserve - Przemyski, Alojzy; Jankowska-Błaszczuk, Małgorzata (Biodiversity: Research and Conservation, 2006)
The studies were conducted on species densities and ecological structure of grassland patches which had developed following removal of the shrubs and trees. The observations were made in the forest clearing reserve - the refugium of xerothermic grassland vegetation situated in the Ponidzie region (Poland). The researches were carried out on plots, which were established in the ecotone zone between forest and xerothermic grasslands as well as in the central part of the clearing. The analyses of species cover in recently revealed gaps in the ecotone zone showed a tendency for decline in species richness and strong dominance of the group of forest species. The analogous comparison of the species richness and composition of the gaps in the central part of the reserve indicated that the patches were being overgrown mainly by grassland species predominantly frequent in the surrounding area. Nevertheless, the characteristic feature of both cases was the diminishing density of species from the grassland group in gap areas. Summing up, we can conclude that in both cases, the gap areas, no matter if in the central part or in the ecotone zone, have been colonized predominantly by species transgressed from neighbouring sites - in the ecotone zone these were forest species, in grassland gaps the major group of colonisers constituted the grassland species.